Enzymatic amplification of human cytomegalovirus sequences by polymerase chain reaction. - Hsia, K (1989)
Polymerase chain reaction (PCR) amplification was used to detect human cytomegalovirus (HCMV) sequences. The fragments selected for amplification were fragments of 130 and 152 base pairs (bp) located at two opposite ends of HCMV strain AD169 EcoRI fragment D. Amplification of the 152-bp DNA was consistently greater than that of the 130-bp DNA. At the optimal Mg2+ concentration of 5 mM, specific PCR amplification of 152-bp DNA with Taq polymerase was sensitive; only one AD169-infected fibroblast cell or 0.01 pg of AD169 fragment D DNA was needed for detection. This specific amplification was also found with various clinical HCMV isolates and peripheral blood cells and urine from patients. In 37 urine samples analyzed simultaneously by PCR and by virus cultivation, identical results were found in 35 samples, while 2 scored positive only by PCR. This suggests that specific amplification of 152-bp DNA is sensitive and can be used for rapid detection of HCMV infections.